Abstract Improving Students’ Mathematic Achievement By Using Task Method At The Third Grade Students In Sd Negeri 07 Pinang Sebatang Barat, Kecamatan Tualang Kabupaten Siak In Academic Year 2015/2016 - Hindun Hindun (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Elementary school level, basic skills, reading, writing and arithmetic are given on the subjects of mathematics and Indonesian language.Math and Indonesian lessons are very useful and fundamental lessons.But the condition of learning in class III SDN 07 Pinang Sebatang Barat these two subjects have not achieved maximum results.This is evident from the results of mathematics and Indonesian replication given only 10 students (42%) of 32 students the total number of students in class III SDN 07 pinang a western trunk that get the value in accordance with KKM.Berarti than 50% of students' mathematics learning results are still below minimum completeness criteria (KKM), which has been determined by the school.The KKM has been determined by the school for mathematics ≥ 60, while the Indonesian language is ≥ 65 Based on the identification and analysis of the above problems found many problems: 1) is giving task method can improve learning outcomes of mathematics to the subject of simple fractions in Class III SD Negeri 07 Pinang Sebatang Barat Kecamatan Tualang in Academic Year 2015/2016? 2) Does the process skills approach can improve learning outcomes Indonesian Listen to the story on the subject of the third grade students of SDN 07 Pinang Sebatang Barat Kecamatan Tualang in academic year 2015/2016? As subject in this Classroom Action research is a third grade students of SD Negeri 0 7Pinang SebatangKecamatan Tualang Siak in the academic year 201 5/201 6 with the total number of students 32 people consisting of 18 male students - male and 18 female students with ability to understand the different subjects.This study uses learning tools consisting of: syllabus, learning implementation plan (RPP), Student Worksheet (LKS), and further training. The conclusion that: 1) Application of the method of assignment in the learning process can improve the results of teaching and learning mathematics at third grade students of SD Negeri 07 Pinang Sebatang Barat Kecamatan Tualang in academic Year 201 5/201 6, with the average results of students in cycle 1 reaches 63, 78 and in cycle 2 reaches 70.78. 2) Implementation other Method in the learning process can improve student Indonesian learning outcomes at third grade students in SD Negeri 07 Pinang Sebatang Barat Kecamatan Tualang in academic year 2015/2016, with the average student learning outcomes in cycle 1 reached 64.06 and in cycle 2 reaches 71.71.